Mosquito Larval Density, Incidence Rate, CFR, and Domestic Water Storage System During Transmission of Dengue Hemorrhagic Fever in Kupang, East Nusa Tenggara, 2012 - Ragu Harming Kristina; Irfan - (Pusat Kedokteran Tropis, 2012)
Introduction: The number of dengue cases in the city of Kupang was quite high when compared to previous years. Number of deaths due to dengue fever was also considered high. When compared between the months of January, February and March 2012 with January, February and March of 2011, there was an epidemiologically significant increase in cases (the increase was higher than 2-fold). In epidemiological sense, this situation was considered as dengue outbreak or extraordinary event.Objectives: To calculate and investigate mosquito larval density (density rate), incidence rate, case fatality rate (CFR), and water storage system in community.Methods: This research was a descriptive survey study using a cross sectional design.The size of samples to be studied was 300 samples allocated evenly to the 10 kelurahan (urban villages), including Bakunase, Kuanino, Bonipoi, Nunhila, Oetete, Sikumana, TDM, Pasir Panjang, Penfui, and Kelapa Lima.Results: The mosquito larval density in Kupang consisting of CI = 39.80%, HI = 67%, BI = 1.97 and LFI (larva free index) = 33%. Incidence Rate (IR) =0.3% and Case Fatality Rate (CFR)= 1.2%. Types of containers used here were Drum, water tanks, Jars/buckets/pot, and others (kettles, jerrycans, cooking pots). The majority of containers used were drums. Water storage duration was on average 3-7 days.Conclusion: The density of larvae in the city is quite high based on CI, HI, BI, and LFI. Themortality rate (CFR) is far in excess of the national standard, where it is directly proportional to the density of Aedes larvae. The drumis themost commonly container used. Water distribution systemfromthe PDAMof the Kupang city constitutes amajor factor causing people to store water for a long time.Keywords: larval density, Incidence Rate, CFR, water storage system